Các nhân tố ảnh hưởng đến sự hình thành trữ lượng nước dưới đất lưu vực sông Sài Gòn - Chân, Ngô Đức; Kỳ, Nguyễn Việt (Vietnam Journal of Earth Sciences, 2012)
BummaryInfluenced factors to the formulation of groundwater reserve in Saigon river basinOriginating source of groundwater reserve is not only one of research speciality in hydrogeology, but also an important information for groundwater resources exploitation management and protection. Basedon existing research results, this paper deals with analysing and determining main natural and artificial factors which have deciding role in formulation of groundwater reserve in Saigon river basin. These factors are separated into 2 groups : natural factors (structure of groundwater system, topographical features, hydrological system and climate) and artificial factors (groundwater exploitation and agricultural).